2008
DOI: 10.1063/1.3012388
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of efficiency droop in InGaN light emitting diodes by coupled quantum wells

Abstract: Light emitting diodes ͑LEDs͒ based on InGaN suffer from efficiency droop at current injection levels as low as 50 A cm −2. We investigated multiple quantum well InGaN LEDs with varying InGaN barrier thicknesses ͑3-12 nm͒ emitting at ϳ400-410 nm to investigate the effect of hole mass and also to find out possible solutions to prevent the efficiency droop. In LEDs with electron blocking layers, when we reduced the InGaN barriers from 12 to 3 nm, the current density for the peak or saturation of external quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
139
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(145 citation statements)
references
References 14 publications
5
139
1
Order By: Relevance
“…5,6 Almost all research on InGaN/GaN symmetric and asymmetric QWs has been of polar material grown in the cdirection with strong polarization and piezoelectric effects. 3,4 Although these effects may be minimized in LED structures if the QWs are fabricated in non-polar orientations, there have been few such investigations, including studies of (11-20) "aplane" InGaN/GaN QWs on (10-12) r-plane sapphire and aplane SiC as well as studies of (10-10) "m-plane" InGaN/GaN QWs on (100) LiAlO 2 substrates. [7][8][9] In a prototypical study, the reduced quantum-confined Stark effect in a-plane GaN/AlGaN QW structures reduced the redshift with increasing QW width as compared to structures grown in the c-direction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Almost all research on InGaN/GaN symmetric and asymmetric QWs has been of polar material grown in the cdirection with strong polarization and piezoelectric effects. 3,4 Although these effects may be minimized in LED structures if the QWs are fabricated in non-polar orientations, there have been few such investigations, including studies of (11-20) "aplane" InGaN/GaN QWs on (10-12) r-plane sapphire and aplane SiC as well as studies of (10-10) "m-plane" InGaN/GaN QWs on (100) LiAlO 2 substrates. [7][8][9] In a prototypical study, the reduced quantum-confined Stark effect in a-plane GaN/AlGaN QW structures reduced the redshift with increasing QW width as compared to structures grown in the c-direction.…”
mentioning
confidence: 99%
“…1,2 InGaN/GaN coupled QW structures are known to improve device performance by facilitating carrier transport within the active region, dramatically increasing the light-output power of the devices at high current density. 3,4 However, despite intensive research on stress and defect generation, polarization fields, localization of charge carriers, exciton binding, confinement of the charge carriers by the QW barriers, and delocalization of charge carriers apart from nonradiative recombination centers, no approach adequately explains how these factors combine to affect nonradiative recombination and reduce device efficacy. 5,6 Almost all research on InGaN/GaN symmetric and asymmetric QWs has been of polar material grown in the cdirection with strong polarization and piezoelectric effects.…”
mentioning
confidence: 99%
“…It has been observed that a substantial EL efficiency reduction (by 4-5 times) occurs when an electron blocking layer (EBL) is not employed, regardless of whether polar or nonpolar orientations of GaN are used [64]. In InGaN LEDs, while not being the entire reason at this juncture, relatively low hole injection (due to relatively low hole doping of p-GaN) and/or poor hole transport inside the active region (due to large hole effective mass if quantum wells constitute the active region) could exacerbate the electron overflow, as electrons need accompanying holes in the active region for recombination [13,65]. Theoretical calculations also indicate that electron density in equilibrium with the lattice even well above the room temperature would not have a sufficient Boltzmann tail to surpass the barrier present for notable electron spillover [66].…”
Section: Optical Excitation Experiments and Auger Processmentioning
confidence: 99%
“…To evaluate IQEs of the LED structures, excitation density dependent resonant photoluminescence (PL) experiments were conducted at 15 K and room temperature for single and quad DH LEDs with varying SEI thickness with the aid of a frequency-doubled Ti:Sapphire laser (385 nm wavelength) to ensure excitation of the DH active regions only [11,65]. Because carriers under resonant excitation are confined inside the active region already, the overflow effect is eliminated in the optical experiment.…”
Section: Iqe and Eqe Of Single And Multi Active Layer Dh Structuresmentioning
confidence: 99%
“…Over the past few years, people have proposed various physics mechanisms to explain the phenomenon such as Electron leakage [1][2], Auger recombination [3][4], carrier delocalization [5], polarization effect [6][7], poor hole injection efficiency [8][9], and the quantum confined Stark effect [10]. In [11] and [12], interband Auger processes are being gradually confirmed to be one of the most important physics mechanisms for efficiency droop in the InGaN LED, as well as possible solutions to address the interband Auger using new active region materials.…”
Section: Introductionmentioning
confidence: 99%